Mitochondrial DNA, molecular genetics and human mitochondrial diseases - Scheffler, Immo (Henry Stewart Talks, 2009)
Mitochondria: structure and function, Mitchell's chemiosmotic hypothesis, The mammalian mitochondrial genome: replication, Transcription, Gene expression, Non-Mendelian inheritance of mtDNA, Mutations and heteroplasmy, Mitochondrial diseases, Reactive oxygen species and aging, Mitochondria and neurodegenerative diseases, The metabolic syndrome